Verbal and Nonverbal Devices of Legal Rhetoric in the Defence Speech - Khujaniyazova Khilola Turayevna, Kasimkhadjayeva Mutabar Alimdjanovna, Khidirova Maftuna Ilhom Qizi (International Journal of Control and Automation, 2021)
This article discusses legal rhetoric, focusing on issues such as the role, methods, and importance of verbal and nonverbal means in lawyers’ speech. While some scholars have emphasized the importance of paralinguistic devices in lawyers’ speech, others have argued in their research that paralinguistic devices have their place and meaning in every speech. The article focuses on similar problems and solutions and highlights important factors in research work. In literary works, the use of paralinguistic devices in our daily lives is vividly reflected in this article, which makes the speech of lawyers more effective, more profound. The examples given in it serve to further enrich the article as to how lawyers use non-linguistic devices in their defensive speech and what these paralinguistic devices mean from various publications.